Biomarkers predictive of response to pembrolizumab in head and neck cancer. (7th December 2022) - Pfister, David G.; Haddad, Robert I.; Worden, Francis P.; Weiss, Jared; Mehra, Ranee; Chow, Laura Q. M.; Liu, Stephen V.; Kang, Hyunseok; Saba, Nabil F.; Wirth, Lori J.; Sukari, Ammar; Massarelli, Erminia; et al.
Abstract: Background: We performed an integrated biomarker evaluation in pembrolizumab‐treated patients with R/M HNSCC enrolled in KEYNOTE‐012 or KEYNOTE‐055. The relationship between biomarkers and HPV status was explored. Methods: We evaluated PD‐L1 (combined positive score [CPS]), TMB, T‐cell‐inflamed gene expression profile (Tcellinf GEP), and HPV status. Associations between biomarkers were evaluated by logistic regression (ORR) and Cox regression (PFS, OS). Results: Two hundred and fifty‐seven patients (KEYNOTE‐012, n = 106; KEYNOTE‐055, n = 151) had TMB data available; of these, 254 had PD‐L1 and 236 had Tcellinf GEP. TMB, PD‐L1, and Tcellinf GEP were each significantly associated with ORR ( p < 0.01). Kaplan–Meier curves at prespecified cutoffs generally showed PFS and OS separation in the anticipated direction for these biomarkers, except for OS and TMB. TMB did not correlate with PD‐L1 or Tcellinf GEP (Spearman ρ = −0.03 and ρ = −0.13, respectively); PD‐L1 and Tcellinf GEP were moderately correlated (Spearman ρ = 0.47). In multivariate models, TMB, PD‐L1, and Tcellinf GEP were each independently predictive for ORR ( p < 0.001). ORR was higher in patients with high versus low levels of biomarkers when dichotomized using prespecified cutoffs; patients with higher versus lower levels of TMB and PD‐L1 or TMB and Tcellinf GEP had the highest ORRs. Within HPV subgroups, higher versus lower distributions of biomarkers (PD‐L1, TMB, and Tcellinf GEP) were associated with response. HPV detection by p16‐immunohistochemistry and WES showed good concordance (81%); results were generally similar by HPV status, regardless of the detection method. Conclusions: TMB and the inflammatory biomarkers PD‐L1 and Tcellinf GEP, assessed alone or together, may be useful for characterizing clinical response to pembrolizumab in R/M HNSCC. Abstract : TMB and inflammatory biomarkers PD‐L1 and T‐cell‐inflamed GEP, assessed alone or together, may be useful for characterizing clinical response to pembrolizumab in R/M HNSCC. Greater responses to pembrolizumab were associated with higher levels of TMB and inflammatory biomarkers than were lesser responses, an observation that was consistent regardless of HPV status, suggesting that biomarkers representing complementary measures of tumor antigenicity and a T‐cell‐inflamed tumor microenvironment may be useful in characterizing response to pembrolizumab.